The Effect of Giving Warm Compresses on the Level of Menstrual Pain in Adolescent Girls at the Hidayatus Sholikin Islamic Boarding School in Pembuang Hulu, Central Kalimantan - Susanti, Ria; Wijayanti, Wijayanti; Puji Astuti, Hutari (Universitas Kusuma Husada Surakarta, 2024)
Dysmenorrhea is an individual response to a disruptive state of the endocrine system that can cause pain during menstruation. The cause of the pain is the imbalance of progesterone hormones in the blood. The more severe the pain can disrupt the psychological condition of the individual, where pain stimulates the brain, leading to changes in life, social relationships, feelings of anger, fear, and depression. This study aims to determine the effect of giving warm compresses on the level of menstrual pain in adolescent girls. The research is a Pre-Experimental Design conducted from August 2023 to March 2024. The research population is 222 teenage girls from Islamic Boarding School Hidayatus Sholikin Pembuang Hulu Central Kalimantan, and the sample obtained from a calculation of 68 teenage girls. The sampling technique used is simple random sampling, with the Standard Operating Procedure for the independent variable on the application of warm compresses and the dependent variable with the observation of menstrual pain in teenage girls. Data is analyzed using the Wilcoxon Rank Test on SPSS. The results of the research show that the characteristics of the respondents, with the majority of 43 respondents (63.3%) being 12 years old, 44 respondents (64.7%) having regular menstrual cycles, 31 respondents (45.6%) having a menstrual cycle of 28 days, 36 respondents (52.9%) experiencing menstrual pain (Dysmenorrhea) on the first day, 38 respondents (55.9%) having a high level of menstrual pain in teenage girls before being given warm compresses, and most of 35 respondents (51.5%) having a low level of menstrual pain in teenage girls after being given warm compresses. There is an impact of applying warm compresses on the level of menstrual pain in teenage girls (p value=0.000). The conclusion of this research is that there is an impact of applying warm compresses on the level of menstrual pain in teenage girls.